Respuesta :
Answer:
4x-2y=0
Step-by-step explanation:
Ok
so you need to subtract
(3x+2y=22)-(-x+4y=22)
Use distributive property and take away parenthesis
3x+2y=22+x-4y=-22
----------------------------
3x+2y=22
x-4y=-22
------------------------------
4x-2y=0
Brainliest Please
Answer:
( [tex]\frac{22}{7}[/tex] , [tex]\frac{44}{7}[/tex] )
Step-by-step explanation:
3x + 2y = 22 ....... (1)
- x+ 4y = 22 ........ (2)
3 × (2) + (1)
(3x - 3x) + (2y + 12y) = 22 + 66 ( variable "x" is eliminated )
14y = 88
y = [tex]\frac{44}{7}[/tex]
- x + 4( [tex]\frac{44}{7}[/tex] ) = 22
x = [tex]\frac{176}{7}[/tex] - [tex]\frac{154}{7}[/tex] = [tex]\frac{22}{7}[/tex]
( [tex]\frac{22}{7}[/tex] , [tex]\frac{44}{7}[/tex] )